SENYAWA SCOPOLETIN DARI EKSTRAK KLOROFORM - Restu Putri, ; Tukiran, (Matematika dan Sains, 2010)
A phenolic compound from the stem bark of Sandoricum koetjape Merr.(local name: kecapi) had been isolated for the first time. The compound isolated was gained from chloroform extract after doing a series of fractionation using various chromatographied method, including vacuum liquid chromatography (VLC), flash chromatography (FC), and preparative-thin layer chromatography (P-TLC), usually monitored by TLC. Based on spectroscopic data i.e. IR, UV-Vis, and GC-MS, it was established that the isolate was scopoletin